187k views
4 votes
Solve: X = -3y - 17 2x + 3y = -7​

User ShmulikA
by
4.9k points

2 Answers

5 votes

Answer:

X = 2 x − 10

y = − 2 /x 3 − 7 /3

Explanation:

To get this you must solve y first. There are no variables to x so find y and put it into the equation. Substitute it and find X

User Dimitar Asenov
by
5.5k points
4 votes

Answer:

x = 10, y = - 9

Explanation:

Given the 2 equations

x = - 3y - 17 → (1)

2x + 3y = - 7 → (2)

Substitute x = - 3y - 17 into (2)

2(- 3y - 17) + 3y = - 7 ← distribute and simplify left side

- 6y - 34 + 3y = - 7

- 3y - 34 = - 7 ( add 34 to both sides )

- 3y = 27 ( divide both sides by - 3 )

y = - 9

Substitute y = - 9 into (1) for corresponding value of x

x = - 3(- 9) - 17 = 27 - 17 = 10

User Mathias W
by
5.0k points